The Influence of Leadership, Work Environment and Job Stress on Employee Job Satisfaction at Football Suppliers and Manufacturers in Pasuruan - Khotimah, Khusniyatul; Adiwati, May Retno (Universitas Kristen Petra dan Ikatan Sarjana Ekonomi Indonesia Cabang Surabaya, 2024)
Human resources are the main asset for a company who are planners and active actors of various activities within the company. Therefore, companies need to accommodate leadership, work environment and employee work stress well so that employee job satisfaction in the company continues to increase. This research aims to determine the influence of leadership, work environment and work stress on employee job satisfaction at football suppliers and manufacturers in Pasuruan. The research method used is a quantitative method and data collection uses a questionnaire using a five-point Likert scale as a measuring tool. The population used in this research was all production employees at football suppliers and manufacturers in Pasuruan with 299 employees. The sample in this research were production employees at football suppliers and manufacturers in Pasuruan, which was still active during the Covid-19 pandemic, had 81 respondents using a purposive sampling technique. The data used is primary data and secondary data, while the analysis used is Partial Least Square (PLS). Based on the results of the research that has been conducted, leadership has a positive and significant influence on the job satisfaction of PT employees. football suppliers and manufacturers in Pasuruan. The work environment has a positive and significant influence on the job satisfaction of employees at football suppliers and manufacturers in Pasuruan. Job Stress has a positive and insignificant influence on employee job satisfaction on football suppliers and manufacturers in Pasuruan.